Encyclopedia of Life Sciences 2010
DOI: 10.1002/9780470015902.a0022853
|View full text |Cite
|
Sign up to set email alerts
|

Animals and Their Unicellular Ancestors

Abstract: Animals belong to the Opisthokonta, one of the major divisions of the eukaryotic Tree of Life. This supergroup also includes other well‐known groups such as fungi and choanoflagellates, in addition to some newly discovered unicellular taxa as the Ichthyosporea or the Filasterea. To unveil the origin of animal multicellularity, it is vital to understand the evolution of their single‐celled relatives, as they might hold key genetic clues that might help us understand how the unicellular ancestors of animals beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Consistent with this idea, colony formation and morphology are influenced by presence of a specific bacterial prey species 47. Another group of metazoan relatives, the ichthyosporeans, also transitions between a unicellular amoeboid state and simple spherical colonies 48, 49. The cellular slime mold Fonticula alba exhibits facultative multicellularity very similar to Dictyostelium , despite being more closely related to fungi than to social amoebae 39.…”
Section: Multicellularity As a Plastic Trait In Metazoan Ancestorsmentioning
confidence: 79%
“…Consistent with this idea, colony formation and morphology are influenced by presence of a specific bacterial prey species 47. Another group of metazoan relatives, the ichthyosporeans, also transitions between a unicellular amoeboid state and simple spherical colonies 48, 49. The cellular slime mold Fonticula alba exhibits facultative multicellularity very similar to Dictyostelium , despite being more closely related to fungi than to social amoebae 39.…”
Section: Multicellularity As a Plastic Trait In Metazoan Ancestorsmentioning
confidence: 79%
“…Recent phylogenetic and phylogenomic analyses have shown that the opisthokonts also include several unicellular lineages (Steenkamp et al 2006). These include the nucleariids (Amaral-Zettler et al 2001), Fonticula alba (Brown et al 2009), the filastereans (Shalchian-Tabrizi et al 2008), the ichthyosporeans (also known as DRIPs or mesomycetozoeans) (Ragan et al 1996), Corallochytrium limacisporum (Raghu-Kumar 1987), and the choanoflagellates (Carr et al 2008) (for a review see Paps and Ruiz-Trillo 2010). Although we have some knowledge of the diversity of metazoans, fungi, and choanoflagellates, our current understanding of the evolutionary diversity of the other opisthokont lineages is very poor.…”
mentioning
confidence: 99%
“…Holozoa is the group that contains Metazoa and their closest unicellular relatives, namely Choanoflagellata, Filasterea, Ichthyosporea, and Plurimorfea, the latter with an uncertain phylogenetic position in relation to Ichthyosporea (Paps and Ruiz-Trillo, 2010;Torruella et al, 2015;Hehenberger et al, 2017). Holozoa also contains some exclusively environmental clades, mainly within choanoflagellates and ichthyosporeans (del Campo and Ruiz-Trillo, 2013).…”
Section: Diversity and Novelty Of Holozoamentioning
confidence: 99%
“…This lack of knowledge of eukaryotic diversity also occurs in Opisthokonta, the superclade that comprises Metazoa, Fungi and several unicellular lineages (Ruiz-Trillo et al, 2008;Paps and Ruiz-Trillo, 2010;Torruella et al, 2012). These unicellular opisthokonts are understudied compared to their multicellular relatives, even though they are essential for better understanding key evolutionary transitions, including those that took place at the origins of both animals and fungi (Ruiz-Trillo et al, 2007;Richter and King, 2013;Brunet and King, 2017;Richards et al, 2017;Sebé-Pedrós et al, 2017).…”
Section: Introductionmentioning
confidence: 99%